2014
DOI: 10.1016/j.bbi.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

In vivo suppression of NK cell cytotoxicity by stress and surgery: Glucocorticoids have a minor role compared to catecholamines and prostaglandins

Abstract: Most in vitro and ex-vivo studies indicate a profound suppression of NK cell cytotoxicity (NKCC) by glucocorticoids; while catecholamines and prostaglandins were reported both to suppress and to enhance NKCC. However, methodological considerations hinder our ability to deduce from these findings to the impact of endogenous release of these factors on in vivo levels of NKCC and their implications to NK-dependent resistance to pathologies in living humans or animals. Here we used an in vivo approach that sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 61 publications
4
48
0
Order By: Relevance
“…In 2 of the 3 groups of patients in our study, we observed an increase in the postoperative plasma concentrations, and those undergoing chronic BB therapy experienced a smaller postoperative decrease in the NK cell function. Similar results have been demonstrated in experimental studies, but the actual relevance of our findings may be illustrated by the results in a recent publication by Rosenne et al, who demonstrated that catecholamines are significant contributors to low NKCC after laparotomy in animals, although this phenomenon only partially explains the protumoral effects of surgery [10,12,22,23].…”
Section: Discussionsupporting
confidence: 90%
“…In 2 of the 3 groups of patients in our study, we observed an increase in the postoperative plasma concentrations, and those undergoing chronic BB therapy experienced a smaller postoperative decrease in the NK cell function. Similar results have been demonstrated in experimental studies, but the actual relevance of our findings may be illustrated by the results in a recent publication by Rosenne et al, who demonstrated that catecholamines are significant contributors to low NKCC after laparotomy in animals, although this phenomenon only partially explains the protumoral effects of surgery [10,12,22,23].…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, this may occur through a more prolonged exposure, which was evident herein to exert a direct in vitro NK suppressive effects in the presence of plasma, and was reported by in vivo studies [16]. Additionally, suppression of NKCC may occur through (i) indirect effects of stress hormones on NKCC, such as through reduction in Th1 cytokine levels [43], (ii) through direct suppression of NKCC by catecholamines and PGs when locally released at supra-systemic levels [26, 3234], and/or (iii) through suppression of non-circulating unique NK cell subpopulations [4446] of different susceptibility to stress hormones.…”
Section: Discussionmentioning
confidence: 57%
“…However, several ex-vivo studies in humans and animals have suggested that no such suppression occurs in vivo [21, 22], and a recent in vivo animal study has supported this suggestion, indicating specific conditions under which corticosterone may exerts some effects [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Activation of the sympathetic nervous system leads to release of stress hormones such as epinephrine and norepinephrine (NE), which signal via adrenergic receptors on tumor cells, resulting in diminished efficacy of conventional chemotherapy and promotion of tumor metastasis, inflammation, and other prosurvival pathways (6)(7)(8)(9)(10)(11)(12). Although molecular events that have direct effects on tumor cells have been well documented, the effects of adrenergic signaling on the tumor stroma are not well understood.…”
Section: Introductionmentioning
confidence: 99%